Scaffolding Content in an Online Content and Language Integrated Learning (CLIL) Module - Laetitia Monbec (Cranmore Publishing, 2020)
This paper describes how the content knowledge in an Academic English Writing, Content and Language Integrated Learning (CLIL) module 'Colour: Theory, meaning and practice' was adapted to online delivery to adjust to the COVID pandemic social distancing measures. The module is delivered to small groups of approximately 15 students, and, in face-to-face mode, the pedagogy exploits this by engaging students in small group discussions, dialogue, questioning, and oral presentations. In a face-to-face mode, the content is unpacked and scaffolded dialogically throughout the tutorials. Shifting to an online delivery in a well-equipped setting (technology was widely available to tutor and students) involved deliberate scaffolding of content and orchestration of the various technologies and the various interaction they afford in order to achieve the same learning outcomes. In doing this, the author found that the Legitimation Code Theory dimension of semantic gravity, which conceptualises content knowledge in terms of levels of abstraction, was helpful to guide the scaffolding of content over the tutorial. The paper describes the content and the aim of the module and one specific tutorial on Colour in Film leading to a written assignment. It then briefly explains how Legitimation Code Theory was used in this context. The tutorial stages are described to demonstrate how students were provided different types of activities to engage gradually with increasingly abstract and theoretical content.